2013 IEEE/RSJ International Conference on Intelligent Robots and Systems 2013
DOI: 10.1109/iros.2013.6696387
|View full text |Cite
|
Sign up to set email alerts
|

Minimal representation for the control of the Adept Quattro with rigid platform via leg observation considering a hidden robot model

Abstract: Previous works on the Gough-Stewart (GS) platform have shown that its visual servoing using the observation of its leg directions was possible by observing only three of its six legs but that the convergence to the desired pose was not guarantied. This can be explained by considering that the visual servoing of the leg direction of the GS platform was equivalent to controlling another robot, the 3-UPS that has assembly modes and singular configurations different from those of the GS platform. Considering this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…Recently, two of the authors of the present paper demonstrated in [19] that these points could be explained by considering that the visual servoing of the leg direction of the GS platform was equivalent to controlling another robot "hidden" within the controller, the 3-UPS 1 that has assembly modes and singular configurations different from those of the GS platform. A similar property was shown for the control of the Adept Quattro for which another hidden robot model, completely different from the one of the GS platform, was found [21]. All theoretical results were validated through experimental works in [22].…”
Section: Introductionsupporting
confidence: 67%
“…Recently, two of the authors of the present paper demonstrated in [19] that these points could be explained by considering that the visual servoing of the leg direction of the GS platform was equivalent to controlling another robot "hidden" within the controller, the 3-UPS 1 that has assembly modes and singular configurations different from those of the GS platform. A similar property was shown for the control of the Adept Quattro for which another hidden robot model, completely different from the one of the GS platform, was found [21]. All theoretical results were validated through experimental works in [22].…”
Section: Introductionsupporting
confidence: 67%
“…There are many papers that propose the kinematics of the parallel manipulator using the geometric relationship only. [5][6][7] In this paper, the inverse kinematics of a quattro-parallel manipulator is derived as the vector formulation.…”
Section: Kinematics and Dynamics Of An Aerial Parallel Manipulatormentioning
confidence: 99%
“…It should be noticed that, in several cases for robots with a lower mobility, the last joint should be changed so that, if the number of observed legs is inferior to the number of real legs, the hidden robot keeps the same mobility (see [12]). Moreover, we have presented above the most general methodology, but not the most elegant.…”
Section: How To Define the Legs Of The Hidden Robotsmentioning
confidence: 99%
“…In many cases, a hidden robot leg architecture can be obtained such that less modifications w.r.t the real leg are achieved. For example, for the Quattro [12] made of R-{2-UU} legs for which the parallelogram links are observed ({2-UU} subchain links), the R-PPP chain of the hidden robot leg (which is indeed a{R-PPP}-{2-UU} leg) could be fully-equivalently replaced by a planar parallelogram (Π joint) [12].…”
Section: How To Define the Legs Of The Hidden Robotsmentioning
confidence: 99%
See 1 more Smart Citation